2020
DOI: 10.3390/v12060619
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Norovirus Is Chronically Shed by Immunocompromised Pediatric Hosts

Abstract: Noroviruses are a leading cause of gastroenteritis worldwide. Although infections in healthy individuals are self-resolving, immunocompromised individuals are at risk for chronic disease and severe complications. Chronic norovirus infections in immunocompromised hosts are often characterized by long-term virus shedding, but it is unclear whether this shed virus remains infectious. We investigated the prevalence, genetic heterogeneity, and temporal aspects of norovirus infections in 1140 patients treated during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…The application of this general approach to norovirus has been limited, but use of the simple and effective method for enriching viral genomes prior to sequencing described here should make viral evolutionary studies in MNoV and HNoV systems more tractable. Recent studies have indicated that distinct HNoV variants emerge in immunocompromised hosts, and indeed that this chronically-shed virus maintains infectivity [48,[69][70][71]. Careful tracking of viral genomic characteristics during chronic HNoV infection has the potential to facilitate identification of novel variants emerging in immunocompromised settings that could seed future epidemics.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The application of this general approach to norovirus has been limited, but use of the simple and effective method for enriching viral genomes prior to sequencing described here should make viral evolutionary studies in MNoV and HNoV systems more tractable. Recent studies have indicated that distinct HNoV variants emerge in immunocompromised hosts, and indeed that this chronically-shed virus maintains infectivity [48,[69][70][71]. Careful tracking of viral genomic characteristics during chronic HNoV infection has the potential to facilitate identification of novel variants emerging in immunocompromised settings that could seed future epidemics.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Therefore, these variants were thought to have limited transmissibility; on the other hand, it is also possible that family members were immune to re-infection with GII.4 quasispecies based on exposure to NoV during the primary infection. In other studies, transmission of NoV from chronically infected persons has been shown [ 23 ], and continuous shedding of infectious virus has been detected based on the ability to replicate in human intestinal enteroid (HIE) cultures in vitro [ 24 ]. Molecular epidemiology studies suggest that a substantial proportion of NoV infections in immunocompromised patients originally thought to be nosocomial were acquired in the community, and nosocomial outbreaks where persons with immunodeficiency disorders are the source are rare [ 25 , 26 ].…”
Section: Epidemiology Of Norovirusmentioning
confidence: 99%
“…In a case series of 13 HSCT recipient children with chronic NoV infection who needed enteral/parenteral nutritional support [ 42 ], CD3 recovery was associated with clearance of NoV from fecal samples; however, the role of NoV-specific antibodies in clearance of NoV was not evaluated. In a study by Davis et al [ 24 ], NoV infection continued despite white blood cell count recovery due to possible continued use of immunosuppressives. The relevance of T cells in gut-associated lymphoid tissue in controlling NoV infection is unknown [ 43 ].…”
Section: Immunity To Norovirusmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral shedding duration and the length of time individuals remain infectious have important implications for transmission and control of coronavirus disease 2019 (COVID-19). Immunocompromised individuals shed viruses such as influenza, cytomegalovirus, and norovirus longer than immunocompetent persons [ 1 , 2 ]; however, little is known about the effect of immunosuppression on duration of SARS-CoV-2 culture or polymerase chain reaction (PCR) positivity. At least 1 study demonstrated prolonged SARS-CoV-2 PCR positivity in kidney transplant recipients, albeit without a comparison group [ 3 ], and rare cases highlight potential for prolonged, intermittent shedding with immunosuppressive medications [ 4 , 5 ].…”
mentioning
confidence: 99%